2010
DOI: 10.1017/s1463423610000344
|View full text |Cite
|
Sign up to set email alerts
|

Training health visitors in cognitive behavioural and person-centred approaches for depression in postnatal women as part of a cluster randomised trial and economic evaluation in primary care: the PoNDER trial

Abstract: Aim: This paper aims to describe the training preparation for health visitors who took part in the intervention arm of a cluster randomised controlled trial and economic evaluation of training for health visitors -the POstNatal Depression Economic evaluation and Randomised (the PoNDER) trial. A secondary aim is to make available, by electronic links, the training manuals developed for and used for the cognitive behavioural approach (CBA) and the person-centred approach (PCA) training for the health visitors. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…A common element of the training, preceding specific approach-based skills, involved developing empathic relationships. Two experienced psychotherapist practitioner trainers delivered the training, which was carried out according to a manual, 19 and was agreed by a training reference group, comprising experienced academically-based psychotherapy and counselling trainers. In addition, health visitors were asked to audio record their intervention sessions (with the women's consent), so that session treatment fidelity could be checked.…”
Section: Summary Of the Ponder Trialmentioning
confidence: 99%
“…A common element of the training, preceding specific approach-based skills, involved developing empathic relationships. Two experienced psychotherapist practitioner trainers delivered the training, which was carried out according to a manual, 19 and was agreed by a training reference group, comprising experienced academically-based psychotherapy and counselling trainers. In addition, health visitors were asked to audio record their intervention sessions (with the women's consent), so that session treatment fidelity could be checked.…”
Section: Summary Of the Ponder Trialmentioning
confidence: 99%
“…There were improved outcomes for depressed women in the study areas, where health visitors received this additional training, over those in the control areas (Morrell et al, 2011). Further, women viewed as "low risk" were significantly less likely to develop PND in the study areas than in the control areas, where health visitors had received no extra training (Brugha et al, 2011).…”
Section: Identifying Women Affected By Post Natal Depressionmentioning
confidence: 99%
“…In their trial of interventions to identify and treat post-natal depression (PND), Morrell et al (2009Morrell et al ( , 2011 provided health visitors with specialist knowledge on PND symptom identification and trained them to deliver cognitive behavioural (CBA) and person-centred interventions (PCA) to eligible women. There were improved outcomes for depressed women in the study areas, where health visitors received this additional training, over those in the control areas (Morrell et al, 2011).…”
Section: Identifying Women Affected By Post Natal Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 A research conducted in India showed that 23.34% of Lady Health Visitors showed "excellent knowledge", 52.32% of them had "good knowledge" and 23.34% had "average knowledge" on majority of the subjects taught to them. 9 A research paper stated that 78% had adequate knowledge to practice individually. 10 According to a study, the introduction of maternal and child health intervention progamme led to a significant improvement (p < 0.05) in the performance skills of lady health visitors related to antenatal, postnatal and newborn care.…”
Section: Original Articlementioning
confidence: 99%